The Effect of Interpersonal Communication of Outpatient Registration Officers on Patient Satisfaction at dr. Esnawan Antariksa Air Force Hospital - Galuh Patricia Arda Tama; Nanda Aula Rumana; Daniel Happy Putra; Dina Sonia (HM Publisher, 2023)
Interpersonal communication is a need and ability that health workers must have so that patients feel happy with the services provided. The research was conducted with a focus on outpatients because researchers wanted to know the effect of interpersonal communication of outpatient registration officers on patient satisfaction. The research method uses inferential analysis with a quantitative approach. Statistical test using Chi-square test. The sampling method used in this research is accidental sampling. Based on the research results, the description of interpersonal communication of officers who are categorized as poor interpersonal communication is 36 (51.4%), officers who are categorized as good interpersonal communication are 34 (48.6%). The description of the satisfaction of patients who are categorized as dissatisfied is 36 (51.4%), the satisfaction of patients who are categorized as satisfied is 34 (48.6%) and there is an influence between the interpersonal communication of registration officers and patient satisfaction at dr. Esnawan Antariksa Air Force Hospital found that the p-value was 0.000 < 0.05. By calculation, the odds ratio obtained a value of 15.98, meaning that interpersonal communication has a 15 times risk factor for patient satisfaction at dr. Esnawan Antariksa Air Force Hospital. In conclusion, there is an effect between interpersonal communication of outpatient registration officers and patient satisfaction at dr. Esnawan Antariksa Air Force Hospital.